ESCRT III Complex in Trypanosomatids: Unraveling the role of Vps32 in membrane scission required processes - Barrera, Nadia Maricel (2018)
The ESCRT (Endosomal Sorting Complex Required for Transport) is a machinery that drives a diverse collection of membrane remodeling events such as endocytosis, multivesicular body biogenesis, autophagy, release of enveloped viruses, reorganization of the nuclear envelope and cytokinetic abscission during mitosisexit. ESCRTIII is the effector sub-complex for the reason that is capable to form filaments and spirals, which produces membrane constrictions. Vps32 is the most abundant protein in ESCRTIII and its dynamic over membranes is given for its molecular structure that alternates between a monomeric-closed state to polymeric-open state. Here we investigate the conservation of Vps32 in replicative stages of Trypanosoma cruzi and Trypanosoma brucei. The Saccharomyces cerevisiae gene corresponding to the Vps32 (Snf7) wasused to screen TriTrypDB databases. We found the T. cruzi orthologue (TcVps32) which have two alleles in CL Brener strain: TcCLB.511589.250 (Esmeraldo) and TcCLB.511229.100 (Non Esmeraldo). These sequences were used to screen T. brucei database resulting in a high-scored target: Tb427tmp.01.1390. Protein domains, secondary structure composed of alpha helices and charges distribution (a basic N-terminal and an acid C-terminal) were determinate showing a high conservation among eukaryotic cells. To perform a functional characterization and detect regulatory regions of TcVps32, T. cruzi epimastigote cells were transfected with pRIBOTEX vector containing the following hemagglutinin (HA) tagged constructs: i) full length TcVps32 (HA-TcVps32), ii) deletion of helix 5 (HA-TcVps32D5), iii) deletion of helix 5 and the linker region (HA-TcVps32D5L) and finally, iii) deletion of helix 4, linker and helix 5 (HA-TcVps32D4y5L).Additionally, In T. brucei procyclic form we designed an RNAi strategy where a 405bp of TbVps32 was cloned into the p2T7 vector (TbVps32-RNAi) allowing a tetracycline inducible downregulation. We confirmed the successful silencing of TbVps32 by RT-PCR after 48h of silencing induction and after 72 h we observed that the viability of the parasites was severely affected. In both models of replicative forms (T. cruzi epimastigotes overexpressing TcVps32 and T. brucei procyclic forms TbVps32 RNAi induced), we observed alterations in cell cycle progression, presumably in cytokinesis due to the presence of aberrant flagellums and the abnormal nucleus-kinetoplast congurations.